AN IMPROVING FISHERMAN PRODUCT QUALITY AND FISHING PERFORMANCE BASED ON IOT - Sandy Andhana Surbakti; Solly Aryza; Adi Sastra P Tarigan (Sean Institute, 2022)
The function of technology in fisheries is a renewable innovation that is needed by fishermen. From fishing patterns that were previously only based on tides and the position of the moon, now using technology fishermen can find out which locations have a lot of fish so that they are more efficient and don't take a long time and luck. in catching fish in the sea. The design of a system that initializes fish objects using sonar by utilizing marine acoustics is expected to help increase fishermen's catches. The system is built by utilizing the Arduino UNO microcontroller and echosounder as well as an Android smartphone that will display readings from the echo sounder.